Pengaruh Manajemen Laba dan Struktur Modal Terhadap Nilai Perusahaan Pada Perusahaan Tambang yang Terdaftar di Bursa Efek Indonesia - Ice, Ice; Mas'ud, Arifuddin; Asni, Nur (Universitas 17 Agustus 1945 Jakarta, 2025)
This study intends to investigate the impact of earnings management practices along with capital structure in the firm value of mining unit companies listed in the Indonesia Stock Exchange (IDX) during 2019-2023. From a population of 82 mining companies, a sample of 63 companies was selected using purposive sampling, resulting in a total of 315 observations. Panel data regression analysis using EViews 12 shows that earnings management has a negative impact in firm value, meaning that an increase in earnings management tends to decrease the firm value. Oppositely, capital structure has a positive impact, indicating that an increase in capital structure can enhance firm value. Simultaneously, earnings management along with capital structure have a significant impact, highlighting that managing both aspects is crucial in determining firm value.